Diffusion and Ion-Exchange in Low-Permeability Rocks: Laboratory-Based X-Ray Methods - Cadieux, Charles (Université d'Ottawa / University of Ottawa, 2024)
Safe storage of radioactive wastes from nuclear power production represents a challenge faced by several jurisdictions. In recent decades, proposals for long-term storage into geological formations have sparked interest in solute migration through low-permeability materials. Diffusion and ion-exchange are key mechanisms that govern transport through rocks in which porewater is immobile, but there are challenges associated with studying these processes efficiently and accurately at the laboratory scale with current methods. In this research, an existing X-ray radiography technique was modified successfully to allow for the study of non-reactive tracer diffusion in a very low porosity (<0.5%), heterogenous granite from the Lac du Bonnet Batholith (Manitoba, Canada). Additionally, a novel energy-dispersive X-ray fluorescence (EDXRF) technique was developed to study simultaneous diffusion of non-reactive and reactive tracers in the Queenston Formation shale (Bruce nuclear site, Ontario, Canada). The two methods produced coherent tracer concentration profiles through the transient stage of diffusion and allowed for the successful estimation of an effective diffusion coefficient of 3.1×10⁻¹⁴ m²/s for I in the granite and pore diffusion coefficients for I and Cs in the shale of 6.1 ± 0.4×10⁻¹¹ m²/s and 9.5 ± 1.3×10⁻¹¹ m²/s, respectively, as well as a cation exchange capacity of 1.8 ± 0.7 meq/100g and a selectivity coefficient for the exchange of Na⁺ for Cs⁺ of 2.3 ± 0.2 for the shale. The techniques that were developed represent additional tools for efficient, in-situ study of diffusion and ion-exchange in low-permeability rocks. There is potential for extending their scope to different applications, and surely to the study of additional tracers and materials.
Keywords: Diffusion; Ion-exchange; X-Ray; Radiography; Fluorescence